Iron deficiency and the effectiveness of the BNT162b2 vaccine for SARS-CoV-2 infection: A retrospective, longitudinal analysis of real-world data. - Lilac Tene; Avraham Karasik; Gabriel Chodick; Dora I A Pereira; Henrik Schou; Sandra Waechter; Udo-Michael Göhring; Hal Drakesmith (PLoS ONE)
Background Iron plays a key role in human immune responses; however, the influence of iron deficiency on the coronavirus disease 2019 (COVID-19) vaccine effectiveness is unclear. Aim To assess the effectiveness of the BNT162b2 messenger RNA COVID-19 vaccine in preventing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and COVID-19-related hospitalization and death in individuals with or without iron deficiency. Methods This large retrospective, longitudinal cohort study analyzed real-world data from the Maccabi Healthcare Services database (covering 25% of Israeli residents). Eligible adults (aged ≥16 years) received a first BNT162b2 vaccine dose between December 19, 2020, and February 28, 2021, followed by a second dose as per approved vaccine label. Individuals were excluded if they had SARS-CoV-2 infection before vaccination, had hemoglobinopathy, received a cancer diagnosis since January 2020, had been treated with immunosuppressants, or were pregnant at the time of vaccination. Vaccine effectiveness was assessed in terms of incidence rates of SARS-CoV-2 infection confirmed by real-time polymerase chain reaction assay, relative risks of COVID-19-related hospitalization, and mortality in individuals with iron deficiency (ferritin <30 ng/mL or transferrin saturation <20%). The two-dose protection period was Days 7 to 28 after the second vaccination. Results Data from 184,171 individuals with (mean [standard deviation; SD] age 46.2 [19.6] years; 81.2% female) versus 1,072,019 without (mean [SD] age 46.9 [18.0] years; 46.2% female) known iron deficiency were analyzed. Vaccine effectiveness in the two-dose protection period was 91.9% (95% confidence interval [CI] 83.7-96.0%) and 92.1% (95% CI 84.2-96.1%) for those with versus without iron deficiency (P = 0.96). Of patients with versus without iron deficiency, hospitalizations occurred in 28 and 19 per 100,000 during the reference period (Days 1-7 after the first dose), and in 19 and 7 per 100,000 during the two-dose protection period, respectively. Mortality rates were comparable between study groups: 2.2 per 100,000 (4/181,012) in the population with iron deficiency and 1.8 per 100,000 (19/1,055,298) in those without known iron deficiency. Conclusions Results suggest that the BNT162b2 COVID-19 vaccine is >90% effective in preventing SARS-CoV-2 infection in the 3 weeks after the second vaccination, irrespective of iron-deficiency status. These findings support the use of the vaccine in populations with iron deficiency.